2020
DOI: 10.1111/cge.13696
|View full text |Cite
|
Sign up to set email alerts
|

Three novel patients with epileptic encephalopathy due to biallelic mutations in the PLCB1 gene

Abstract: Biallelic mutations in the PLCB1 gene, encoding for a phospholipase C beta isoform strongly expressed in the brain, have been reported to cause infantile epileptic encephalopathy in only four children to date. We report here three additional patients to delineate the phenotypic and genotypic characteristics of the disease. Our three patients were one sporadic case with an intragenic homozygous deletion and two cousins with the homozygous p.(Arg222*) nonsense variant in PLCB1. These patients had severe to profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Inhibitory interneurons are stimulated by cholinergic input and loss of PLCβ1 results in disruption of PKC activity leading to a deficit in GABAergic inhibition [174]. In J o u r n a l P r e -p r o o f human patients, loss of PLCβ1 also results in infantile epileptic encephalopathy [175][176][177] (Table 2). This is a rare event and to date, only seven cases have been identified.…”
Section: Plcβ1mentioning
confidence: 99%
“…Inhibitory interneurons are stimulated by cholinergic input and loss of PLCβ1 results in disruption of PKC activity leading to a deficit in GABAergic inhibition [174]. In J o u r n a l P r e -p r o o f human patients, loss of PLCβ1 also results in infantile epileptic encephalopathy [175][176][177] (Table 2). This is a rare event and to date, only seven cases have been identified.…”
Section: Plcβ1mentioning
confidence: 99%
“…Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84] [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99] [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115] KIF5A [179] are associated with amyotrophic lateral sclerosis, but these genes might be novel target for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuzaki et al [55], Shepard et al [56], Lennertz et al [57], Klemettilä et al [58], Ullah et al [59], Kim et al [60], Sasayama et al [61], Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84], CXCL11 [85], EGR1 [86], CALB1 [87], BDNF (brain derived neurotrophic factor) [88], TERT (telomerase reverse transcriptase) [89], NEFL (neurofilament light) [90], SNAP25 [91], RPH3A [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99], STXBP5L [100], HCRTR2 [101], SYP (synaptophysin) [102], SYT10 [103], PRKCE (protein kinase C epsilon) [104], NRG1 [105], KISS1 [106], NRXN3 [107], RAB3A [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115], GAP43 [116], TTR (transthyretin) [117], CXCR2 [118], IL1R2 [119], CXCR4 [120], CCR2 [121], MYOCD (myocardin) [122], S100A12 […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in the next base after the exon (c.99+1G>A) in early infantile epileptic encephalopathy 177 and (c.2930+1G>A) in patients with West syndrome has been identified. 178 Additionally, recent studies have shown several novel nonsense mutations associated with epileptic encephalopathy, including c.550C>T (p.Arg184*), 179 c.664C>T (p.Arg222*) 180 and c.1332T>A (p.Tyr444*) 178 within West syndrome.…”
Section: Cryptic Genetic Variations Of Plc Isozymes In Brain Disordersmentioning
confidence: 99%